1996
DOI: 10.1007/bf02246646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clonidine on the human acoustic startle reflex

Abstract: The present study investigated in healthy human volunteers whether clonidine reduced the amplitude of the acoustic startle reflex and whether this effect, if found, was due to an accelerated rate of habituation. Subjects were presented with startle-eliciting noise-bursts after intravenous (iv) infusion of clonidine (1.5 microgram/kg) and saline on separate days. Clonidine significantly reduced the amplitude of the acoustic startle reflex (as indexed by the eyeblink component) relative to the saline treated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 19 publications
11
36
2
Order By: Relevance
“…These studies show that lack of ␣ 2C AR expression is associated with increased startle reactivity, reduced prepulse inhibition of the startle reflex, and isolation-induced attack latency, whereas overexpression of ␣ 2C AR produces the opposite effects. Consistent with these data, in humans, the ␣ 2 AR agonist clonidine and the ␣ 2 AR antagonist idazoxan reduce and facilitate the acoustic startle response, respectively (31,32). The role of ␣ 2C AR in modulating working memory has also been characterized (4).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…These studies show that lack of ␣ 2C AR expression is associated with increased startle reactivity, reduced prepulse inhibition of the startle reflex, and isolation-induced attack latency, whereas overexpression of ␣ 2C AR produces the opposite effects. Consistent with these data, in humans, the ␣ 2 AR agonist clonidine and the ␣ 2 AR antagonist idazoxan reduce and facilitate the acoustic startle response, respectively (31,32). The role of ␣ 2C AR in modulating working memory has also been characterized (4).…”
Section: Resultsmentioning
confidence: 60%
“…Briefly, membranes (ϳ20 g) were incubated with 27 M phosphoenolpyruvate, 0.6 M GTP, 0.1 mM cAMP, 0.12 mM ATP, 50 g/ml myokinase, 0.05 mM ascorbic acid, and 2 Ci of [␣- 32 P]ATP in a buffer containing 40 mM HEPES, pH 7.4, 1.6 mM MgCl 2 , and 0.8 mM EDTA for 30 min at 37°C. These conditions minimize the stimulation of adenylyl cyclase, which is observed at high agonist concentrations (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have shown that the a 2 -AR agonist clonidine decreases startle after systemic administration in humans (Kumari et al, 1996) and rats (Davis et al, 1977), and after spinal (Davis and Astrachan, 1981) or intra-amygdaloid (Schulz et al, 2002) administration in rats. The almost totally abolished startle reflex of WT mice after Dex 10 and especially 30 mg/kg was likely due to its sedative effect.…”
Section: Discussionmentioning
confidence: 96%
“…The a 2 -AR agonist clonidine attenuates (Kumari et al, 1996) and the antagonist yohimbine enhances (Morgan et al, 1993) the startle response in humans, but the receptor subtype(s) mediating these effects is unclear. a 2 -ARdependent modulation of PPI has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that the EMG startle reflex amplitude can be reduced by sedative drugs of different classes, for example, benzodiazepines (diazepam: Scaife et al, 2005), 5HT 2 receptor antagonists (ketanserin: Graham et al, 2002), a 2 -adrenoceptor agonists (clonidine: Kumari et al, 1996;Abduljawad et al, 1997Abduljawad et al, , 2001, tricyclic antidepressants (amitriptyline: Phillips et al, 2000a), and atypical antipsychotics (clozapine and quetiapine: Graham et al, 2001Graham et al, , 2004. In contrast to the EMG startle response, the AEP is relatively resistant to sedative drugs, with only the benzodiazepines reducing N1/P2 amplitude consistently (Lader, 1977;Bond et al, 1983;Pooviboonsuk et al, 1996;Curran et al, 1998;Abduljawad et al, 2001;Scaife et al, 2005).…”
Section: Introductionmentioning
confidence: 99%